Evaluation of the SH-SY5Y cell line as an in vitro model for potency testing of a neuropeptide-expressing AAV vector - Zanker, Jeanette; Hüser, Daniela; Savy, Adrien; Lázaro-Petri, Sara; Hammer, Eva-Maria; Schwarzer, Christoph; Heilbronn, Regine (Frontiers in Molecular Neuroscience, 2023)
Viral vectors have become important tools for basic research as well as clinical gene therapy over the past years. However, in-vitro testing of vector-derived transgene function can be challenging when specific post-translational modifications are needed for biological activity. Likewise, neuropeptide precursors need to be processed to yield mature neuropeptides. SH-SY5Y is a human neuroblastoma cell line commonly used due to its ability to differentiate into specific neuronal subtypes. Here we evaluate the suitability of SH-SY5Y cells in a potency assay for neuropeptide-expressing adeno-associated virus (AAV) vectors. We looked at the impact of neuronal differentiation, compared single-stranded (ss)AAV and selfcomplementary (sc)AAV transduction at increasing MOIs, RNA transcription kinetics, as well as protein expression and mature neuropeptide production. SH-SY5Y cells proved highly transducible with AAV1 already at low MOIs in the undifferentiated state and even better after neuronal differentiation. Readouts were GFP-or neuropeptide mRNA expression. Production of mature neuropeptides was poor in undifferentiated cells. By contrast, differentiated cells produced and sequestered mature neuropeptides into the medium in a MOI-dependent manner.